Pengaruh Penerapan Green Accounting, Kinerja Lingkungan dan Ukuran Perusahan terhadap Nilai Perusahaan pada Perusahaan Sektor Energi yang Bergerak di Bidang Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Eneng Fauziah; Indra Cahya Kusuma; Didi (Economic Reviews Journal, 2025)
This study aims to determine the effect of green accounting which can be seen from the existence of CSR activities in the company's annual report, environmental performance which can be seen from the PROPER report issued by KLHK, company size which can be seen from the total assets in the company's annual report and the firm value as measured by Tobin's Q, as well as to determine the effect of green accounting, environmental performance, and company size on firm value. The data used in this study were analyzed using multiple linear regression with Eviews 12 software. The population of this study were energy sector companies operating in the mining sector that were listed on the BEI from 2019 to 2023. The research sample was selected using a purposive sampling method so that a total of 11 were obtained. company. The results of this study indicate that green accounting has a significant effect on firm value, environmental performance has a significant effect on firm value, company size has no effect on firm value, and green accounting, environmental performance and company size have an effect on firm value.